Effects of Fibre Length and Fibre Loading on Tensile and Flexural Properties of Luffa Cylindrica Reinforced Polylactic Acid Composite - Bukar, M.; Aji, I. S.; Mshelia, Z. A.; Hammajam, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study examines the effects of fibre length and fibre loading on the tensile and flexural properties of Luffa cylindrica reinforced polylactic acid (PLA) composites. Luffa cylindrica fibres, a natural and biodegradable reinforcement material, were incorporated into PLA at varying fibre lengths (1 mm, 3 mm, and 5 mm) and fibre loadings (10%, 20%, 30%, 40%, and 50%) to assess their impact on mechanical performance. The results revealed that both tensile and flexural properties were significantly affected by fibre length and loading. Optimal mechanical properties were observed at 30% fibre loading with a 3 mm fibre length, where tensile strength reached 28.52 MPa and flexural strength peaked at 77.81 MPa. However, higher fibre loadings (40% and 50%) led to a reduction in strength due to poor interfacial adhesion and fibre wetting. Shorter fibre lengths (1 mm) contributed to a higher tensile modulus, suggesting that compact fibre arrangements resist deformation more effectively. This study highlights the potential of Luffa cylindrica fibres as effective reinforcements in PLA composites, offering valuable insights for sustainable material development.